Down in the Vale: Corporate Globalization, Unions on the Defensive, and the USW Local 6500 Strike in Sudbury, 2009–2010 - Peters, John (Labour / Le Travail, 2010)
Abstract This article assesses one of the longest private sector strikes in Canadian history — the United Steelworkers (usw) Local 6500 strike at Vale in Sudbury, 2009-2010. It argues that in the context of corporate globalization and the recent financial crisis, Vale took full advantage of its economic power to win major concessions from Local 6500. The usw’s community, political, and corporate campaigns were unable to pressure the company or the federal and provincial government effectively and the result was that a powerful international corporation prevailed in its efforts to erode the material well-being of its Canadian workforce. Such a defeat, alongside the recent collective bargaining concessions by auto workers in Canada and the United States, is a major blow to the North American labour movement.  Trade unions must therefore develop more successful strategies of resistance and begin the process of reforming and rejuvenating themselves as organizations defending workers. If this is not done the future of North American labour is bleak indeed.